Heart rate and heart rate variability in lambs, measured by biologgers, during transport and its relationship to basal cortisol concentration - Isabella Manenti; José A. Abecia; Irene Viola; Paola Toschi; Francisco Canto; Silvia Miretti (Italian Journal of Animal Science)
In this study, we investigated the relationship between heart rate variability (HRV) and basal cortisol levels in lambs in the course of a short transport event. Fourteen lambs received a subcutaneously implanted biologger that was capable of recording body temperature (T) and HR at one-minute intervals. In addition, lambs wore collars that held triaxial accelerometers, which were used to record locomotor activity (LA) before and during transport (73 km). Saliva samples for cortisol measurements were collected 24 h and 4 h before transport and 1 h post-transport. Based on basal cortisol concentrations, lambs were assigned to one of two groups, low cortisol (LC) or high cortisol (HC). HR and HRV were measured at 1 h before, during, and 1 h after transport. Mean HR was similar at all three points, but HRV variables (SDNN and RMSSD) were higher (p < 0.01) during transport than they were 1 h before and 1 h after transport, particularly in the LC group. Accelerometry data revealed that the LC lambs displayed a lower (p < 0.001) LA than did the HC lambs before and during transport. In conclusion, lambs that had lower baseline cortisol levels were better adapted physiologically to the stress of transport, as reflected by their greater HRV response and calmer behaviour, than were those who had higher cortisol levels. Subcutaneous biologgers have been shown to be a powerful tool for detecting subtle physiological responses to stressors, even in situations where traditional markers such as HR or cortisol levels do not vary significantly.HIGHLIGHTS Lambs with lower basal cortisol showed higher HRV and calmer behaviour during transport. Subcutaneous biologgers detected stress responses not seen in HR or cortisol levels alone. High cortisol lambs were more active and less physiologically adapted to transport stress.